One Laptop per Child and its Implications for the Process of Written Language Learning: A Case Study in Brazil - Silvia de Oliveira Kist; Marie Jane Soares Carvalho; Juliano de Vargas Bittencourt (Universidad Autónoma de Baja California, 2013)
This is a case study on the reading and writing practices of six year old children engaged in the daily use of digital technology, conducted in a public school in Porto Alegre (RS/Brazil) and made possible by the One Laptop per Child (OLPC) project. Its aim was to investigate the practices carried out by students and the possibilities and conditions under which the computer can become a tool that enables them to enter the "literate world". The students' practices were examined based on three units of analysis: practices proposed by a teacher, spontaneous practices and representative cases. These practices were categorized into three areas: literacy, fluency of written language and technological fluency. The research began with a theoretical proposal that had to be modified as a result of the study, and emphasizes the importance of pedagogical proposals for children in the initial process of written language learning.